+0  
 
+1
235
1
avatar+396 

deleted.

 Sep 13, 2019
edited by sinclairdragon428  Sep 13, 2019
edited by sinclairdragon428  Nov 20, 2019

Best Answer 

 #1
avatar+25237 
+2

Compute 

\(\mathbf{\dfrac{(n-1)!n}{(n+1)!}}\)

 

\(\begin{array}{|rcll|} \hline && \mathbf{\dfrac{(n-1)!n}{(n+1)!}} \quad | \quad \boxed{(n-1)!n = n!} \\ &=& \dfrac{n!}{(n+1)!} \quad | \quad \boxed{n!(n+1) = (n+1)!} \\ &=& \dfrac{n!}{n!(n+1)} \\ &=& \mathbf{\dfrac{1}{ n+1 }} \\ \hline \end{array} \)

 

laugh

 Sep 13, 2019
 #1
avatar+25237 
+2
Best Answer

Compute 

\(\mathbf{\dfrac{(n-1)!n}{(n+1)!}}\)

 

\(\begin{array}{|rcll|} \hline && \mathbf{\dfrac{(n-1)!n}{(n+1)!}} \quad | \quad \boxed{(n-1)!n = n!} \\ &=& \dfrac{n!}{(n+1)!} \quad | \quad \boxed{n!(n+1) = (n+1)!} \\ &=& \dfrac{n!}{n!(n+1)} \\ &=& \mathbf{\dfrac{1}{ n+1 }} \\ \hline \end{array} \)

 

laugh

heureka Sep 13, 2019

12 Online Users

avatar
avatar